Performance and carcass characteristics of lambs with three subcutaneous fat thicknesses in the loin - de Macedo, Francisco de Assis Fonseca; Gualda, Thiago Peres; Mexia, Alexandre Agostinho; de Macedo, Filipe Gomes [UNESP]; Dias, Franciane Barbieri; Mora, Natália Holtz Alves Pedroso (My University, 2014)
The objective of this study was to evaluate productive and economic performances and quantitative carcass characteristics of 1/2Dorper + 1/2Santa Inês (1/2D-SI) and purebred Santa Inês (SI) lambs slaughtered with different subcutaneous fat thicknesses (SFT). Thirty-four lambs (16 SI and 18 1/2D-SI) were confined and fed a total diet for an average daily weight gain of 0.300 kg. The subcutaneous fat thickness was measured by ultrasound (between the 12th and 13th ribs) and weekly weighing, and the lambs were slaughtered as they reached the pre-established SFT of 2.0, 3.0 and 4.0 mm. Breed group had no effect on productive performance. With regard to SFT, the final body weight was highest in the animals slaughtered with 4.0 mm. The economic evaluation provided an increasing net income with increase in SFT. The commercial and true yields were affected by the SFT at slaughter. For the cuts, the yield of the loin of crossbred animals was higher than that of Santa Inês lambs. The loin measurements showed no difference between breed groups. The lambs slaughtered with 2.0 and 3.0 mm of fat thickness presented the best feed conversion; however, those slaughtered with 4.0 mm of fat thickness had better economic results.
Keywords: Dorper; Production costs; Santa inês; Ultrasound